2020
DOI: 10.1038/s41372-020-00840-7
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Pain, Agitation, and Sedation Scale’s use, reliability, and validity: a systematic review

Abstract: The Neonatal Pain, Agitation, and Sedation Scale (N-PASS) is recommended by the American Academy of Pediatrics to measure neonatal pain and sedation. However, little is known regarding its reliability and validity for diverse neonatal subpopulations. Twenty-nine studies were included in our review, demonstrating broad application of N-PASS and good or excellent reliability and validity for various neonatal subpopulations. Our systematic review found N-PASS to be valid and reliable for many but not all neonatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 45 publications
0
29
0
Order By: Relevance
“…For preterm infants, there are validated measures for the evaluation of pain, including the Neonatal Pain, Agitation and Sedation Scale (N-PASS), however this is targeted to assess acute pain and was not designed to assess withdrawal measures in the setting of prolonged pharmacological sedation [10][11][12][13] . The Withdrawal Assessment Tool -Version 1 (WAT-1) metric is the best tool currently validated for diagnosis and assessment of iatrogenic withdrawal in older pediatric patients with meta-analysis data demonstrating high reliability and validity [14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…For preterm infants, there are validated measures for the evaluation of pain, including the Neonatal Pain, Agitation and Sedation Scale (N-PASS), however this is targeted to assess acute pain and was not designed to assess withdrawal measures in the setting of prolonged pharmacological sedation [10][11][12][13] . The Withdrawal Assessment Tool -Version 1 (WAT-1) metric is the best tool currently validated for diagnosis and assessment of iatrogenic withdrawal in older pediatric patients with meta-analysis data demonstrating high reliability and validity [14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…There are up to 65 scales to evaluate pain or sedation in children in a preverbal stage of development [ 15 , 16 ]. The American Academy of Pediatrics (AAP) recommends using the following 5 scales to assess neonatal pain ( Table 1 ): Neonatal Facial Coding System (NFCS), Premature Infant Pain Profile-Revised (PIPP-R), Neonatal Pain, Agitation and Sedation Scale (N-PASS), Behavioral Indicators of Infant Pain (BIIP) and Acute Pain in Newborns/Douleur Aiguë du Nouveau-né (APN/DAN) [ 15 , 17 ].…”
Section: How To Assess Neonatal Pain: Pain Assessment Scalesmentioning
confidence: 99%
“…Based on the previous literature, Beltramini et al (2017), Pölkki et al (2014) and Morgan et al (2020) argue that there are several suitable validated scales for measuring procedural pain in infants. In our study, nurses reported that most of the pain scales named in the questionnaire were unfamiliar to them and they had not used them in their daily work.…”
Section: Procedural Pain Assessment In Infantsmentioning
confidence: 99%
“…A systematic review by Maaskant et al (2016) indicates that the COMFORT scale is sufficiently reliable in relaying pain information. Pölkki et al (2014) developed in close collaboration with nurses the Neonatal Infant Acute Pain Assessment Scale (NIAPAS) and Morgan et al (2020) adds that the Neonatal Pain Agitation Sedation Scale (N-PASS) is a suitable instrument in evaluating pain and sedation for most infants' populations. In addition, Face, Legs, Activity, Cry, Consolability scale (FLACC) has found a suitable tool for pain assessment in infants (Beltramini et al, 2017;Crellin et al, 2018;Witt et al, 2016).…”
Section: Introductionmentioning
confidence: 99%